2018
DOI: 10.1111/ggi.13472
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic status of subtelomere of peripheral leukocytes corresponds to cardiographic parameters with a sex association

Abstract: Cardiac function correlates not only with telomere length, but also with the distribution of the telomere length and subtelomeric DNA methylation status. These imply that the loss of young cells, the accumulation of old cells and the acceleration of such changes in the cell population relate to phenotypes of cardiac aging with relative sex specificity. Furthermore, the PR interval showed a very close association with telomeric parameters in both sexes. Hence, PR is the most reliable candidate as an indicator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In hypertensive patients, the degree of subtelomeric methylation of long telomeres was often inversely correlated with telomere consumption (Maeda et al, 2011b). Researchers found that cardiac function was related to both telomere length and subtelomeric DNA methylation (Maeda et al, 2018). Maeda et al (2013) also found that subtelomeres were hypomethylated and telomerase activity was decreased in senescent smooth muscle cells.…”
Section: Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In hypertensive patients, the degree of subtelomeric methylation of long telomeres was often inversely correlated with telomere consumption (Maeda et al, 2011b). Researchers found that cardiac function was related to both telomere length and subtelomeric DNA methylation (Maeda et al, 2018). Maeda et al (2013) also found that subtelomeres were hypomethylated and telomerase activity was decreased in senescent smooth muscle cells.…”
Section: Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 99%
“…Cardiovascular and cerebrovascular diseases are common diseases that seriously threaten the health of humans, especially middle-aged and elderly people. Previous studies have shown that cardiovascular and cerebrovascular diseases were significantly associated with subtelomeric DNA methylation and telomere length (Maeda et al, 2011b, 2018). In the future, subtelomeric DNA methylation should be investigated in other cardiovascular and cerebrovascular diseases (such as coronary heart disease, myocardial infarction, stroke, and etc.…”
Section: Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 99%
“…Another study in 222 Japanese patients presenting with several predominantly chronic neurologic conditions investigated ECG measures in relation to semi-quantitatively measured telomere length using Southern blot analysis. The authors report an association with ECG measures including PR-interval, QRS-duration, and QTc [ 28 ]. Importantly, both studies did not adjust for age.…”
Section: Discussionmentioning
confidence: 99%